Comparison of tracheal intubation between sitting position and standing position in COVID-19 patients: A manikin study. Issue 44 (5th November 2021) - Wang, Yong; Shi, Yun; Li, Yong-Xing; Zhong, Ming; Zhuang, Yue-Rong; Huang, Wei; Ma, Wu-Hua
Abstract : Abstract: It is recommended to use visual laryngoscope for tracheal intubation in a Corona Virus Disease 2019 patient to keep the operator farther from the patient. How the position of the operator affects the distance in this setting is not ascertained. This manikin study compares the distances between the operator and the model and the intubation conditions when the operator is in sitting position and standing position, respectively. Thirty one anesthesiologists with minimum 3-years' work experiences participated in the study. The participant's posture was photographed when he performed tracheal intubation using UE visual laryngoscope in standing and sitting position, respectively. The shortest distance between the model's upper central incisor and operator's face screen (UF), the horizontal distance between the model's upper central incisor and the operator's face screen, the angle between the UF line and the vertical line of the model's upper central incisor were measured. The success rate of intubation, the duration of intubation procedure, the first-attempt success rate, the Cormack–Lehane grade, and operator comfort score were also recorded. When the operator performed the procedure in sitting position, the horizontal distance between the model's upper central incisor and the operator's face screen distance was significantly longer (9.5 [0.0–17.2] vs 24.3 [10.3–33.0], P  ≤ .001) and the angle between the UF line and the vertical line of the model's upper central incisor angle was significantly larger (45.2 [16.3–75.5] vs 17.7 [0.0–38.9], P  ≤ .001). There was no significant difference in UF distance when the operator changed the position. Cormack–Lehane grade was significantly improved when it was assessed using visual laryngoscope. Cormack–Lehane grade was not significantly different when the operator assessed it in sitting and standing position, respectively. No significant differences were found in the success rate, duration for intubation, first-attempt success rate, and operator comfort score. The operator is kept farther from the patient when he performs intubation procedure in sitting position. Meanwhile, it does not make the procedure more difficult or uncomfortable for the operator, though all the participants prefer to standing position.